2015
DOI: 10.22329/celt.v8i0.4256
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Feedback, and Revision: Metacognitive Approaches to Undergraduate Essay Writing

Abstract: This paper explores ways in which frequent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Providing feedback is time consuming for evaluators (Ball, Franks, Jenkins, McGrath, & Leigh, 2009;Weaver, 2006;Wiltse, 2002) and emotional for both students and educators (Ekhom et al, 2015). However, feedback can effectively improve student writing when it is clear and understood by the student (Feltham & Sharen, 2015;Parboteeah & Anwar, 2009;Riddell, 2015).…”
Section: Feedback Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Providing feedback is time consuming for evaluators (Ball, Franks, Jenkins, McGrath, & Leigh, 2009;Weaver, 2006;Wiltse, 2002) and emotional for both students and educators (Ekhom et al, 2015). However, feedback can effectively improve student writing when it is clear and understood by the student (Feltham & Sharen, 2015;Parboteeah & Anwar, 2009;Riddell, 2015).…”
Section: Feedback Responsementioning
confidence: 99%
“…Success in improving writing and writing self-efficacy in students is contingent on revision following the feedback process. Riddell (2015) provided several solutions for connecting feedback to the revision process including having students mark sample essays, which served the purpose of helping them identify areas in their own writing where they were failing to clearly explain content. In this present sample, informal peer review was used as a help seeking source by 34.4-40.8% of the student sample indicating that students were open to sharing their work with their peers and trusted their judgement with feedback given.…”
Section: Considerations For Writing Pedagogymentioning
confidence: 99%
“…This study's findings add to the body of evidence signifying the usefulness of metacognitive approaches, feedback, and/or an emphasis on self-improvement to strengthen writing confidence and achievement (Riddell, 2015;Wingate, 2010;Zinn, 1998). The correlation was not as strong as expected, somewhat echoing the disappointing results of Trapman, van Gelderen, van Schooten, &and Hulstijn (2018), who reported that "metacognitive knowledge was not found to be a significant predictor of level of writing proficiency" in their study of low-achieving adolescents (p. 912).…”
Section: Resultsmentioning
confidence: 56%
“…Black, Harrison, Lee, Marshall, & Wiliam, 2003;Riddell, 2015 N/A Feedback is not provided. 7 / 12 mathematics education researcher to independently code examples of PSTs' responses for each question and obtained 95% agreement on the coding of the examples.…”
Section: Discussionmentioning
confidence: 99%